State care services as devices of acceptance to the social body: the case of Afro-descendant migrant mothers in Chile, beneficiaries of the National Child Health Program - Reyes Muñoz, Yafza; Reyes Muñoz, Vania (Frontiers in Human Dynamics, 2024)
Medical anthropology, within the context of healthcare practices, reflects on alterations in the experiences and cultural behaviors of diverse communities in a territory and the asymmetries in interaction with healthcare professionals. Objective of this research is to analyze how the State Childhood Health Program can function as a mechanism of control and acceptance within the Chilean social body for migrant women receiving care through it. The study aims to identify acculturation practices imposed both by healthcare professionals working in health centers and by the migrant women themselves, all in an effort to be recognized by the Chilean societal State. Methodology was developed through a case study in the municipality of Talca, Maule Region, employing semi-structured interviews with nurses working in the Childhood Health Program and open interviews and thematic workshops with migrant women utilizing the program. Results indicate positive perceptions of the program by migrant women, who identify it as a platform for the provision and receipt of care for their children. However, they also acknowledge being judged by those attending to them for not adhering "correctly" to the instructions given for the care of their children living in Chile or for practicing transnational motherhood. On the other hand, nursing professionals reveal racial and class prejudices against Afro-descendant women, especially Haitians. Discussion suggests that this program, recognized regionally as an effective policy in combating infant mortality and morbidity, becomes a tool for acculturation for migrant mothers and their children born in Chile. Both mothers and children are expected to follow the program's guidelines, adopting the same maternal behaviors and attachments as Chilean mothers, i.e., similar ways of mothering and practicing attachment. Conclusions point to the limited opportunities for learning and appreciation of the native cultures of new Chilean generations. Additionally, it reveals that categories of difference such as ethnic-racial identity, gender, and migratory status are woven into the healthcare practices of nurses, emphasizing the mandate for migrant mothers and their children to adhere to instructions in order to be recognized as valid subjects deserving of state and societal acknowledgment, leading to acculturation through assimilation.